2009
DOI: 10.1111/j.1469-1809.2009.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Continental Ancestry of Argentineans from Autosomal, Y‐Chromosomal and Mitochondrial DNA

Abstract: SummaryWe investigated the bio-geographic ancestry of Argentineans, and quantified their genetic admixture, analyzing 246 unrelated male individuals from eight provinces of three Argentinean regions using ancestry-sensitive DNA markers (ASDM) from autosomal, Y and mitochondrial chromosomes. Our results demonstrate that European, Native American and African ancestry components were detectable in the contemporary Argentineans, the amounts depending on the genetic system applied, exhibiting large inter-individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
141
5
17

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(193 citation statements)
references
References 55 publications
(63 reference statements)
30
141
5
17
Order By: Relevance
“…We defined three clusters: African (ASW, YRI and MKK), Asian (CHB, CHD, JPT and GIH), and European-American (CTES, CEU, TSI and MEX). Since American populations have an extensive genetic admixture pattern produced by AmerindiansEuropeans intermarriage [54,55], we decided to pool American and European populations. Within each cluster A118G SNP failed to detect population substructures (all p values > 0.09).…”
Section: Resultsmentioning
confidence: 99%
“…We defined three clusters: African (ASW, YRI and MKK), Asian (CHB, CHD, JPT and GIH), and European-American (CTES, CEU, TSI and MEX). Since American populations have an extensive genetic admixture pattern produced by AmerindiansEuropeans intermarriage [54,55], we decided to pool American and European populations. Within each cluster A118G SNP failed to detect population substructures (all p values > 0.09).…”
Section: Resultsmentioning
confidence: 99%
“…Owing this information, a sample belonging to haplogroup N (from a previous study, Corach et al 2010) was also amplified and the sY1191 deletion described was confirmed for this haplogroup. It is important to highlight that both studies used the same primer sequences to amplify this marker, but differences rely on the number of Q1a3a1 (derivative state for M3) samples used (37 vs. 3) and the paternity confirmation (samples analyzed by Repping et al has an unknown spermatogenic phenotype and DNA was from EBV-transformed lymphoblastoid cell lines).…”
Section: Discussionmentioning
confidence: 99%
“…(YCC 2002) An important remark is that the information available on the Y chromosome sequence in GenBank belongs to one single man's Y chromosome from the European haplogroup R (Jobling and Tyler-Smith 2003;Skaletsky, Kuroda-Kawaguchi et al 2003 (ISOGG 2011). In Argentina, haplogroup R1b1a2 was described as the more prevalent among the urban male population (Corach et al 2010). …”
Section: Y Chromosome Haplogroupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudios previos muestran que existen importantes diferencias regionales, dadas tanto por las cantidades relativas de cada componente como por la intensidad y dirección del proceso de mestizaje (Avena et al 2012;Corach et al 2010;García et al 2011, entre otros).…”
Section: Introductionunclassified